The Regulation of Axon Diameter: From Axonal Circumferential Contractility to Activity-Dependent Axon Swelling - Costa, Ana Rita; Pinto-Costa, Rita; Sousa, Sara Castro; Sousa, Mónica Mendes (Frontiers in Molecular Neuroscience, 2018)
In the adult nervous system axon caliber varies widely amongst different tracts. When considering a given axon, its diameter can further fluctuate in space and time, according to processes including the distribution of organelles and activity-dependent mechanisms. In addition, evidence is emerging supporting that in axons circumferential tension/contractility is present. Axonal diameter is generically regarded as being regulated by neurofilaments. When neurofilaments are absent or low, microtubule-dependent mechanisms can also contribute to the regulation of axon caliber. Despite this knowledge, the fine mechanisms controlling diameter and circumferential tension throughout the lifetime of an axon, remain largely elusive. Recent data supports the role of the actin-spectrin based membrane periodic skeleton and of non-muscle myosin II in the control of axon diameter. However, the cytoskeletal arrangement that underlies circumferential axonal contraction and expansion are still to be discovered. In this Review, we discuss in a critical perspective the existing knowledge on the regulation of axon diameter, with a specific focus on the possible role played by the axonal actin cytoskeleton.